(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to research of problem of functional-categorial paradigm of the participle in semantic-syntactical sentence structure. Basic attention is concentrated on the analysis of the functional potential of the participle in categories: predicativiti, valency, attributivity.